Pembuatan dan pelatihan website Koperasi Kelapa Sawit (KUD Milik Bersama) berbasis android di Desa Bukit Lingkar Kabupaten Indragiri Hulu - Roza Yulida; Rosnita Rosnita; Deby Kurnia; Yulia Andriani; Fanny Septya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The website can be a center of information and communication for them. It is accelerating the flow of information and communication on oil palm growers. The purpose of this service activity is to create an android-based KUD website which contains information about cooperatives and information about oil palm plantations. Community service activities are carried out in Bukit Lingkar Village, one of potential villages in oil palm. In this village, an oil palm village cooperative with the name KUD Milik Bersama has also been established which is a partner in this activity. Activities are integrated with the Student project. Implementation of training activities is socialization and discussion activities. then practice making websites, assistance and coaching. The technical implementation of the activity is a combination of offline and online meetings. It is because Covid 19 pandemic. The implementers in the field are students. The results of this activity include the formation of a cooperative website with the name http: //www.koperasi kudmilikbersama.com, increasing farmers' knowledge and skills regarding media use, including a website with information related to oil palm farming. The establishment of a website manager, which is equipped with a website module.